OPTIMAL SOLUTIONS FOR IMPROVING ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Eva Nurul Candra; Rita Retnowati; Lina Novita (Yayasan Education and Social Center, 2026)
The purpose of this study is to determine the optimal solution from several existing solutions due to limited management resources. The method used to determine the optimal solution is SITOREM (Scientific Identification Theory to Conduct Operation Research Education Management) analysis. The results of the analysis of each indicator in this research variable are as follows: The group of indicators that need to be improved consists of 18 (eighteen) main indicators that show significant contribution but with low actual conditions. The main priorities for indicator improvement include: 1) Mutual cooperation, 2) Honesty, 3) Service, 4) Pioneering, 5) Appreciation of Others, 6) Emotional Stability, 7) Conscientiousness, 8) Openness to Experience, 9) Extraversion, 10) Empathy, 11) Sportsmanship, 12) Sympathy, 13) Reflection, 14) Altruism, 15) Sportsmanship, 16) Civic Virtue, 17) Courtesy, and 18) Self-Development, which are also included in the group of indicators that need improvement. Meanwhile, there are 11 indicators in the group of indicators that are maintained and developed, namely: 1) Morality, 2) Religion, 3) Friendliness, 4) Trust, 5) Integrity, 6) Empowerment, 7) Vision, 8) Modeling, 9) Agreeableness, and 10) Tolerance.